The Role of Religiosity in Moderating Intellectual Capital and ‎Business Performance - Sutapa; Rohman, Abdul; Pujiharto (International Journal of Accounting and Economics Studies, 2025)
Indonesia’s creative batik sector significantly contributes to national economic expansion. Developing intellectual capital through improved ‎human resources, business relationships, cultural assets, and technological advancement is crucial for enhancing operational performance. ‎Religious considerations are equally important for performance improvement. Government officials view intellectual capital as a ‎fundamental approach to strengthening the batik industry outcomes. This investigation analyzes religiosity’s moderating effect on the ‎relationship between human, relational, and structural capital and batik industry performance across Central Java. Through questionnaire ‎surveys of 214 participants and PLS statistical analysis, results demonstrated that human, relational, and structural capital all positively and ‎significantly affected industry performance. Religious factors influenced the relationship between human and structural capital with ‎performance, while showing no moderating effect on relational capital’s performance impact‎.